2019
DOI: 10.1177/0956797618818483
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Prioritization of Self-Referential Stimuli in Working Memory

Abstract: People preferentially attend to external stimuli that are related to themselves compared with others. Whether a similar self-reference bias applies to internal representations, such as those maintained in working memory (WM), is presently unknown. We tested this possibility in four experiments, in which participants were first trained to associate social labels (self, friend, stranger) with arbitrary colors and then performed a delayed match-to-sample spatial WM task on color locations. Participants consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 30 publications
(67 reference statements)
3
72
1
6
Order By: Relevance
“…Firstly, we conducted a replicate experiment to ensure the subjects responded faster under self-associative condition, as compared to other association condition. The result of the present study was consistent with previous research and demonstrated a self-association advantage effect on simple perceptual matching tasks (Sui et al, 2012; Yin et al, 2019). These results suggested that the participants established a temporary connection between label matching and social significance in the perceptual matching task.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Firstly, we conducted a replicate experiment to ensure the subjects responded faster under self-associative condition, as compared to other association condition. The result of the present study was consistent with previous research and demonstrated a self-association advantage effect on simple perceptual matching tasks (Sui et al, 2012; Yin et al, 2019). These results suggested that the participants established a temporary connection between label matching and social significance in the perceptual matching task.…”
Section: Discussionsupporting
confidence: 93%
“…As such, the residual experimental data from 22 subjects were analyzed (see Table 1). On the basis of prior research (Yin et al, 2019), only correct responses with RTs were analyzed with a mixed ANOVA in which the within-subject factor was reference mode (self-reference vs. other-reference) and the between-subject factor was group (typically developing reader vs. dyslexia). A significant main effect was found for reference mode F (1, 16) = 14.09, p < 0.05, η 2 = 0.47, the correct responses with RTs were faster in the self-reference matching condition than other-reference matching condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large prioritisation effect was found in response time, accuracy and sensitivity scores for self shapes compared to those of friend and stranger, and for friend compared to stranger shapes. These effects have been robustly replicated 19 24 and can operate even when associations are not instructed but are learnt over time 25 . Further, self-prioritisation exists even when familiarity is removed from all stimuli, such as when social labels were replaced with unfamiliar abstract symbols associated to the words (you, friend, stranger) before the experiment 26 .…”
Section: Introductionmentioning
confidence: 81%
“…We supposed more social information and heterogeneity carried by multiple faces might be responsible for this discrepancy. To test this idea, future studies could first train participants to associate social information (e.g., self vs. other) with low-level features (e.g., Yin et al., 2019), and then explore the effect of self-construal on ensemble perception. Additionally, as suggested by Sama (2017), the different neural processing pathways recruited by high-level vs. low-level features might also partially explain their discrepant ensemble coding mechanisms, which require further study.…”
Section: Discussionmentioning
confidence: 99%